2018
DOI: 10.48550/arxiv.1810.08179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamics and Feature Extraction by Machine Learning

Shotaro Shiba Funai,
Dimitrios Giataganas

Abstract: Machine learning methods are powerful in distinguishing different phases of matter in an automated way and provide a new perspective on the study of physical phenomena. We train a Restricted Boltzmann Machine (RBM) on data constructed with spin configurations sampled from the Ising Hamiltonian at different values of temperature and external magnetic field using Monte Carlo methods. From the trained machine we obtain the flow of iterative reconstruction of spin state configurations to faithfully reproduce the o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…321) The deep neural network used here is a tool for classifying the phase and is regarded as a blackbox. The properties of the neural network themselves are also interesting to study from the physics view point , 187, especially in relation to the renormalization group [354][355][356][357][358][359][360][361][362] and tensor network. [363][364][365][366][367][368][369][370][371][372] The vulnerability of phase determination against adversarial perturbation is also an interesting topic.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…321) The deep neural network used here is a tool for classifying the phase and is regarded as a blackbox. The properties of the neural network themselves are also interesting to study from the physics view point , 187, especially in relation to the renormalization group [354][355][356][357][358][359][360][361][362] and tensor network. [363][364][365][366][367][368][369][370][371][372] The vulnerability of phase determination against adversarial perturbation is also an interesting topic.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Multiple layers of representation are used to learn distinct features directly from the training data. The similarity between the structure of the DNN and the course-graining schemes in statistical physics inspires many efforts to establish connection between variational RG [21] and unsupervised learning of DNN [22][23][24][25][26][27][28][29][30]. Here, we want to address a different question: how can we train an DNN to obtain an optimal RSRG transformation?…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, tools from Statistical Physics have been applied to analyze the learning ability of RBMs (Decelle et al, 2018;Huang, 2017b), characterizing the sparsity of the weights, the effective temperature, the non- linearities in the activation functions of hidden units, and the adaptation of fields maintaining the activity in the visible layer (Tubiana and Monasson, 2017). Spin glass theory motivated a deterministic framework for the training, evaluation, and use of RBMs (Tramel et al, 2017); it was demonstrated that the training process in RBMs itself exhibits phase transitions (Barra et al, 2016(Barra et al, , 2017; learning in RBMs was studied in the context of equilibrium (Cossu et al, 2018;Funai and Giataganas, 2018) and nonequilibrium (Salazar, 2017) thermodynamics, and spectral dynamics (Decelle et al, 2017); mean-field theory found application in analyzing DBMs (Huang, 2017a). Another interesting direction of research is the use of generative models to improve Monte Carlo algorithms (Cristoforetti et al, 2017;Nagai et al, 2017;Tanaka and Tomiya, 2017b;Wang, 2017).…”
Section: F Generative Models In Physicsmentioning
confidence: 99%